Student Engagement in Science and Social Studies Learning through Project-Based Learning and Poster Media: Keterlibatan Siswa dalam Pembelajaran Ilmu Pengetahuan Alam dan Sosial melalui Project-Based Learning dan Media Poster - Aspita; Sundahry; Nofrianni, Elvima (Indonesian Journal of Innovation Studies, 2025)
General Background: Science and social studies learning in Indonesian elementary schools often relies on teacher-centered instruction, leading to low student motivation and outcomes. Specific Background: Many students in IPAS subjects have not reached the Learning Objectives Achievement Criteria due to limited innovative strategies. Knowledge Gap: Previous studies have shown the value of Project-Based Learning (PBL), yet few have integrated visual media such as posters in elementary IPAS classrooms. Aim: This study investigated how combining PBL with poster media supports active participation and improves student outcomes in grade IV. Results: Conducted as Classroom Action Research in two cycles with 26 students, the study revealed substantial progress. Teacher implementation rose from 72.72% to 90.91%, students in the “very good” activity category increased from 6 to 13, and average scores improved from 74.42 to 82.12, raising mastery from 57.69% to 80.77%. Novelty: Integrating poster media into PBL provided concrete visual support aligned with students’ developmental stage, enhancing engagement and comprehension. Implications: These findings suggest that combining project-based learning with visual aids offers a practical, effective strategy for elementary classrooms to foster motivation, critical thinking, and deeper understanding. Highlight Active student participation increased with project-based learning and poster use. Teacher performance and classroom interaction showed steady improvement. Student achievement in IPAS rose significantly across both research cycles. Keyword Project-Based Learning, Poster Media, Student Engagement, Elementary Education, Science Learning